Does Robotic Milling For Stem Implantation in Cementless THA Result in Improved Outcomes Scores or Survivorship Compared with Hand Rasping? Results of a Randomized Trial at 10 Years. Issue 11 (November 2018) - Nakamura, Nobuo; Sugano, Nobuhiko; Sakai, Takashi; Nakahara, Ichiro
Abstract: Background: Robotic-assisted THA has been promoted as potentially advantageous due to the precision it may afford when machining the proximal femur. However, few reports have compared the long-term clinical results of robotic techniques for femoral component insertion during THA regarding clinical outcomes scores or loosening. Questions/purposes: The purpose of this study was to compare results from a randomized clinical trial (RCT) at a minimum followup of 10 years between robot-assisted and hand-rasped stem implantation techniques with regard to (1) Japanese Orthopaedic Association (JOA) clinical outcomes scores, and (2) aseptic loosening, revision surgery, and heterotopic ossification. Methods: This is a concise followup of a previously reported RCT. In that trial, robot-assisted primary THA was performed on 75 hips (69 patients), and a hand-rasping technique was used on 71 hips (61 patients). Five experienced surgeons at two institutions participated in this trial; all THAs were performed through the posterolateral approach and the patients were treated similarly apart from the method used to prepare the femur. In all, 115 of 130 (88%) of patients initially randomized were available for followup at a minimum of 10 years (mean, 135 months; range, 120–152 months). There was no differential loss to followup between the study groups, and the final study groups here included 64 hips in 59 patients in the robotic group, and 64 hips in 56 patients in the hand-milling group. There were no differences between the study groups in terms of age, sex, diagnosis, body-mass index, or baseline JOA scores. The primary study endpoint was the JOA score, which is scored from 0 to 100, with higher scores representing better function and less pain. Secondary outcomes were revision surgery, and radiographic signs of aseptic loosening and heterotopic ossification as assessed using the four-grade Brooker scale by individuals other than the operating surgeon. Results: At a minimum of 10 years postoperatively, there were no differences between patients treated with robot-assisted surgery or hand rasping in JOA scores (97 ± 5 versus 96 ± 7, mean difference 1.4; p = 0.159). No stems in either group developed aseptic loosening, and there were no revisions in either group. There was no difference between the groups in heterotopic ossification (19 of 64 [30%] in the robot-assisted group versus 12 of 64 [19%] in the hand-rasping group; p = 0.186), severe heterotopic ossification was uncommon in both groups, and no hips developed Grade 4 heterotopic ossification in either group. Conclusions: Clinically and radiographically, THAs performed with robotic milling for stem implantation did not result in better 10-year clinical outcomes scores, or a lower risk of loosening or revision, compared with hand-rasping. We recommend against widespread adoption of robotic milling for stem implantation in primary cementless THAs. Level of Evidence: Level II, therapeutic study.